Upaya Meningkatkan Hasil Belajar Ekonomi Menggunakan Metode Problem Solving pada Peserta Didik Kelas X di SMAN 2 Katingan Hilir - Sumiati, Seri; Ramli, Muhammad (Neraca: Jurnal Pendidikan Ekonomi, 2017)
This study aims to determine the learning activities of students, and increase the results of economic learning after using the Problem Solving method. This study is a Classroom Action Research (CAR). The subjects of this study were students of class X IPS at SMAN-2 Katingan Hilir consisting of 31 students. Analysis of the data used in this study are qualitative data and quantitative data. Research results (1) Learning activities of Class X students at SMAN-2 Katingan Hilir after using the Problem Solving Method became good. The first cycle scores an average of 2.45 with the criteria Good Enough, then in Cycle II the average score obtained by students is 3.8 with good criteria. (2) There is an increase in students' economic learning outcomes by using the Problem Solving Method. in the pre-action process when Pre Test obtained an average value of 73 with 42% classical completeness with criteria not achieved, Cycle I obtained an average value of 82 with classical completeness of 80.64% with criteria not reached and in post test cycle II obtained an average score -ata 92 with 100% classical completeness with Reached criteria.